Cytolytic vaginosis: misdiagnosed as candidal vaginitis. - Cerikcioglu, Nilgun (2004)
OBJECTIVES: In this study, 210 women with vaginal discharge and other symptoms/signs of genital pathology suggestive of vulvovaginal candidiasis (VVC) were involved in order to distinguish true WC and cytolytic vaginosis (CV) cases. METHODS: Fungal cultures, 10% potassium hydroxide (KOH) and Gram stained preparations and pH measurements were performed on the vaginal discharge material of each patient. RESULTS: Fifteen patients (7.1%) were diagnosed with cytolytic vaginosis according to their clinical and microbiological findings, including abundant lactobacilli, fragmented epithelial cells and/or free nuclei due to cytolysis, seen in their discharge materials on microscopic examination, but no fungal growth. CONCLUSIONS: The results of this study may contribute to the reports in the literature indicating the importance of such disorders, which are generally misdiagnosed as candidiasis.